2015
DOI: 10.1016/j.jvb.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Young at heart, old at work? Relations between age, (meta-)stereotypes, self-categorization, and retirement attitudes

Abstract: The aims of this study were to examine how workers? negative age stereotypes (i.e., denying older workers? ability to develop) and negative meta-stereotypes (i.e., beliefs that the majority of colleagues feel negative about older workers) are related to their attitudes toward retirement (i.e., occupational future time perspective and intention to retire), and whether the strength of these relationships is influenced by workers? self-categorization as an ?older? person. Results of a study among Dutch taxi drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 48 publications
3
63
1
6
Order By: Relevance
“…Zacher et al (2010) found that focus on opportunities mediated the positive relationship between job complexity and work performance, such that employees in high-complexity jobs performed better because they had a higher focus on opportunities at work. Moreover, Bal et al (2015) found that overall OFTP mediated the positive relationship between negative age meta-stereotypes and intention to retire, such that workers who had internalized negative age stereotypes had a lower OFTP and consequently, stronger intentions to retire.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Zacher et al (2010) found that focus on opportunities mediated the positive relationship between job complexity and work performance, such that employees in high-complexity jobs performed better because they had a higher focus on opportunities at work. Moreover, Bal et al (2015) found that overall OFTP mediated the positive relationship between negative age meta-stereotypes and intention to retire, such that workers who had internalized negative age stereotypes had a lower OFTP and consequently, stronger intentions to retire.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding attitudinal and behavioral outcomes, Bal et al (2015) found that overall OFTP was associated with lower intentions to retire ( r = -0.19). Moreover, Kochoian et al (2016) investigated and distinguished perceived remaining time and focus opportunities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building upon this line of reasoning, primary studies have found generally positive associations between OFTP and the constructs of job satisfaction (e.g., Weikamp & Göritz, 2016), organizational commitment (e.g., Profili, Sammarra, & Innocenti, 2017), work engagement (e.g., , continuance intentions (e.g., Chen, 2015), achievement motivation (e.g., Froehlich et al, 2016), and motivation to learn . Additionally, negative relationships have been found between OFTP and emotional exhaustion (e.g., Barbieri et al, 2015) and intentions to retire (e.g., Bal, de Lange, et al, 2015). To further codify the nature of these findings, we synthesize all of these relationships in our meta-analysis.…”
Section: Outcomes Of Occupational Future Time Perspectivementioning
confidence: 99%